Methodological aspects of studying the impact of migration on the territorial organization of the population in the Republic of Kazakhstan (Journal of Geography and Environmental Management, 2025)
The article is devoted to the analysis of internal migration processes in Kazakhstan and the assessment of the impact of these processes on the territorial organization of the population. The role of geographical factors (natural conditions, climate, production location, social infrastructure, etc.) is essential in migration processes. Migration can significantly affect the territorial organization of the population and lead to shifts in the demographic structure, population distribution by region and socio-economic development of territories. The aim of the work is to identify and assess the impact of migration on the territorial organization of the population using a geographical approach. The peculiarity of our approach to the study of this topic lies in the comprehensive study of the processes of territorial movement of the population in their interrelation with economic, social, geographical and other factors that cause these movements. In this context, the processes of settlement and migration of the population in the context of the country's regions were studied. The current dynamics of migration processes in Kazakhstan leads to both positive changes in society and an increase in economic, social and environmental problems. Negative consequences are amplified if they are not managed or poorly regulated by the State. This is the relevance of the problem under consideration. The practical significance of the research lies in the fact that knowledge in the field of patterns of migration processes and their management, as well as the interaction of population migration with various aspects of social development can be in demand by those who make decisions in the field of forming a strategy for economic, demographic and migration policy. The information base of the study was made up of official statistical data of the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan, demographic statistics data, data and reports of the Agency for Statistics of the Republic of Kazakhstan, foreign and domestic literary sources, regulatory legal acts of the Republic of Kazakhstan. The results of the study allow us to conclude that migration has a significant impact on the territorial organization of the population in the Republic of Kazakhstan. Based on the results of the study, it is recommended to develop and implement state and regional programs aimed at managing migration processes and adapting migrants, as well as promoting the equitable development of various regions of the Republic of Kazakhstan.
Keywords: migration; territorial organization of the population; demographic structure; economic development